THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY PAYMENT ON FINANCIAL MANAGEMENT IN MSMES - Gunawan, Ade; Aini, Anisa (Proceeding International Seminar of Islamic Studies, 2024)
This research aims to determine and analyze the influence of financial literacy and financial technology payments on financial management, both partially and simultaneously. The approach used in this research is quantitative and associative. The population in this research is all small and medium business actors in the East Medan District. The sample in this research using the Quota sampling technique was 100 small- and medium-sized business actors in the East Medan District. The data collection technique in this research uses a questionnaire (Questioner). The data analysis technique in this research uses the Classical Assumption Test, Multiple Linear Analysis, Hypothesis Testing (t-test and f Test), and Coefficient of Determination. This data processing uses the software program SPSS (statistics package for the social sciences) version 24. Partially, based on the research results, it is concluded that Financial Literacy has a significant positive influence on Financial Management in MSMEs in East Medan District, fintech payments have a significant positive influence on Financial Management in MSMEs in East District, simultaneously Financial Literacy and fintech payments have a significant positive influence on Financial Management in MSMEs in East Medan District.